Progress in Synthesis of Conductive Polymer Poly(3,4-Ethylenedioxythiophene) - Nie, Shisong; Li, Zaifang; Yao, Yuyuan; Jin, Yingzhi (Frontiers in Chemistry, 2021)
PEDOT is the most popularly used conductive polymer due to its high conductivity, good physical and chemical stability, excellent optical transparency, and the capabilities of easy doping and solution processing. Based on the advantages above, PEDOT has been widely used in various devices for energy conversion and storage, and bio-sensing. The synthesis method of PEDOT is very important as it brings different properties which determine its applications. In this mini review, we begin with a brief overview of recent researches in PEDOT. Then, the synthesis methods of PEDOT are summarized in detail, including chemical polymerization, electrochemical polymerization, and transition metal-mediated coupling polymerization. Finally, research directions in acquiring high-quality PEDOT are discussed and proposed.